1925 Ind. Acts 497 § 8 - (:unkn) unknown (General Publisher, 1925)
Prohibited the sale, barter, hire, lend, or giving of pistols or revolvers to minors under the age of twenty-one. Violators guilty of a misdemeanor, fined not more than one hudred dollars, or imprisoned not more than three months, or both fine and imrpisonment.
--
Keywords: TRANSFER - MINORS